2013
DOI: 10.1007/s00284-013-0461-z
|View full text |Cite
|
Sign up to set email alerts
|

Development of Intergeneric Conjugal Gene Transfer System in Streptomyces diastatochromogenes 1628 and Its Application for Improvement of Toyocamycin Production

Abstract: Streptomyces diastatochromogenes 1628, capable of producing toyocamycin (TM), has exhibited a potential biocontrol effect in inhibiting the development of phytopathogens in the agriculture field. In this study, an efficient transformation system was developed using the intergeneric conjugation. This was achieved by optimization of experimental parameters. Under optimal conditions, a maximal conjugation frequency of 4.1 × 10(-4) per recipient was obtained. In order to heterologously express the gene vgb encodin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
15
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 19 publications
(18 citation statements)
references
References 23 publications
2
15
1
Order By: Relevance
“…In contrast with the results of Streptomyces coelicolor [21] and Streptomyces nodosus [25], where the donor-to-recipient ratio did not affect the conjugal efficiency, our results indicated that the maximum efficiency was received with a certain donor-to-recipient ratio of 100:1. Similar results had been observed in Kitasatospora setae [32], Streptomyces lincolnensis [24], and Streptomyces diastatochromogenes 1628 [31], Streptomyces natalensis [33] in which a certain ratio of donor to recipient cell number was required to achieve highest frequency.…”
Section: Resultssupporting
confidence: 81%
See 2 more Smart Citations
“…In contrast with the results of Streptomyces coelicolor [21] and Streptomyces nodosus [25], where the donor-to-recipient ratio did not affect the conjugal efficiency, our results indicated that the maximum efficiency was received with a certain donor-to-recipient ratio of 100:1. Similar results had been observed in Kitasatospora setae [32], Streptomyces lincolnensis [24], and Streptomyces diastatochromogenes 1628 [31], Streptomyces natalensis [33] in which a certain ratio of donor to recipient cell number was required to achieve highest frequency.…”
Section: Resultssupporting
confidence: 81%
“…Compared to the previous studies, in which the transformation efficiency is below 10 −3 [1,26,31,33,48], our study showed high transformation efficiency. The availability of this protocol was confirmed by the 22 double-crossover mutants of glycosyltranferase gene.…”
Section: Discussioncontrasting
confidence: 81%
See 1 more Smart Citation
“…Sun et al (64) found that the ratio of donor to recipient cell numbers was the most influential factor for conjugation into Streptomyces noursei. Also, for Streptomyces diastatochromogenes, the number of spores and their use instead of mycelia, in combination with a cultivation step at 30°C subsequent to the heat shock, were found to be the most important factors (65). In contrast, Du et al (63) achieved the highest conjugation efficiencies for Streptomyces lincolnensis by using mycelia rather than spores as recipients and by addition of 10.3% sucrose to the SM medium (63).…”
Section: Discussionmentioning
confidence: 92%
“…Theoretically, the described procedure provides a promising approach for the ultimate site-specific homologous recombination between this cassette and the bacterial chromosome to generate targeted gene knockouts. However, in practice, it does not work properly for every Streptomyces species, and further optimization is often required to successfully conjugate E. coli with refractory species (62)(63)(64)(65). Various species-dependent parameters which strongly affected the transformation efficiency were identified.…”
Section: Discussionmentioning
confidence: 99%